2019
DOI: 10.1177/1758573219839225
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of chronic anterior radial head dislocations in missed Monteggia lesions in children: A rationale for treatment and pearls and pitfalls of surgery

Abstract: Introduction: The treatment of chronic radial head dislocations after Monteggia lesions in children can be challenging. This article provides a detailed description of the most frequently performed surgical technique: an ulna osteotomy followed by annular ligament reconstruction. Accordingly, we present the clinical and radiological results of 10 paediatric cases. Material and methods: All paediatric patients that had a corrective osteotomy of the ulna for a missed Monteggia lesion between 2008 and 2014 were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…A trans-articular K-wire fixation might be needed to achieve stability after the reduction with or without annular ligament reconstruction. 7 , 8 , 10 Neither situation occurred in the reported Case, which was not a Monteggia or Monteggia-variant fracture. Hence, there was no need for an ulnar osteotomy or lengthening.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…A trans-articular K-wire fixation might be needed to achieve stability after the reduction with or without annular ligament reconstruction. 7 , 8 , 10 Neither situation occurred in the reported Case, which was not a Monteggia or Monteggia-variant fracture. Hence, there was no need for an ulnar osteotomy or lengthening.…”
Section: Discussionmentioning
confidence: 56%
“… 5 Although most children with missed dislocations are initially asymptomatic, they may develop pain, motion limitation, and secondary degenerative changes that eventually necessitate treatment. 6 , 7 Open reduction of missed RHD is necessary to restore satisfactory functional results. Nevertheless, many complications have been reported after surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Mild restriction in protonation is a common complication among operated cases of neglected monteggia fracture. 16 Author contribution…”
Section: Discussionmentioning
confidence: 99%
“…Since expectant treatment of NMF often results in poor outcomes, early surgical intervention is well recommended to decrease complications (5,8,17,22,23,54,63,74). Surgical treatment aims at correcting the angular deformity of the ulnar, stably reducing the radial head and restoring the proper alignment of the radiocapitellar joint (1,2,3,15,19,20,32,40,41,42). Though numerous studies have reported different treatments of NMF, which vary from position to perform osteotomy, options for fixation, and the reconstruction of the annular ligament, there still remains no standard protocol or guidelines (9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,…”
Section: Treatment and Complicationsmentioning
confidence: 99%
“…Plenty of researchers have reported managements of NMF with different outcomes in recent years (9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49). This review aims at summarizing and discussing the current knowledge of NMF, including its definition, its pathophysiological characteristics, the biomechanics of which the radial head slips, and surgical intervention.…”
Section: Introductionmentioning
confidence: 99%